Synthesis and Characteristics of Synthesis and Characteristics of Thiophene Based Monoazo Disperse Dyes on Nylon 6.6 Fabric - S.M, Chindo; I.Y, Chindo; D. E. A, Boryo; K.A, Bello; N. S, Gin (International Journal of Chemistry and Materials Research, 2014)
A series of monoazo disperse dyes has been prepared by diazotizing 2-amino-4(-4-chlorophenylcarbamoyl)-5-methyl-thiophene-3- carboxylic acid ethylester and coupling with N, N-bis (2-cynoethyl) aniline, 3-acetylamino-N,N-diethylaniline and 3-hydroxyl-N,N-dimethyl aniline. The monoazo disperse dyes were characterized by infra red spectra studies. Visible absorption spectra of the dyes were examined in various solvents. The electronic absorption spectra covers a λmax range of 550-650 nm at uniformly high absorption intensity between 2.3 × 104 - 9.2 × 104 l mol-1cm-1. These dyes were applied at 5 % depth on nylon 6.6 fabrics and gave bright intense hues of purple and orange. The colour parameters of the dyed fabrics were measured and the dyes have excellent exhaustion between 79-92 % for nylon 6.6 fabrics, more intense and of very good wash fastness property on nylon 6.6 fabrics. The remarkable degree of levelness and brightness after washing is indicative of good penetration and excellent affinity of these dyes for the nylon 6.6 fabric.